Tren Penelitian Penatagunaan Tanah dalam Kebijakan Pertanahan: Analisis Bibliometrik dari Perspektif Negara Berkembang - Utomo, Dani Lukmito (Tunas Agraria, 2025)
This study aims to map scientific trends and global collaboration dynamics in land use studies in land policy, with a focus on developing countries. Using a bibliometric approach to 124 Scopus-indexed scientific articles during the period 2015–2025, the analysis was conducted using the Bibliometrix package in R Studio software. The results show a significant increase in the number of publications, especially since 2020, but this trend has not been accompanied by a commensurate increase in scientific impact. The most prominent central themes include “land management,” “land tenure,” and “land use planning,” while interdisciplinary approaches linking land issues to climate change and sustainable development continue to strengthen. Countries such as the Netherlands and Ethiopia dominate scientific production and collaboration, reflecting the strengthening involvement of the Global South in the global land discourse. A systematic synthesis of 17 selected articles identified three priority research agendas for further study: analysis of polycentric governance models that synergize various systems and actors; causal measurement of the impacts and trade-offs between land certification programs, food security, and ecosystem integrity; and economic-political studies of geospatial technologies to prevent new forms of digital land grabbing. These research agendas are expected to facilitate the transition from mere land administration to transformative, adaptive, and equitable land governance for developing countries.   Penelitian ini bertujuan untuk memetakan tren keilmuan dan dinamika kolaborasi global dalam studi penatagunaan tanah dalam kebijakan pertanahan, dengan fokus pada negara berkembang. Menggunakan pendekatan bibliometrik terhadap 124 artikel ilmiah terindeks Scopus selama periode 2015–2025, analisis dilakukan dengan menggunakan Bibliometrix package pada perangkat lunak R Studio. Hasil menunjukkan peningkatan signifikan dalam jumlah publikasi, terutama sejak 2020, namun tidak diikuti oleh peningkatan dampak ilmiah yang sebanding. Tema sentral yang paling menonjol meliputi “land management”, “land tenure”, dan “land use planning”, sementara pendekatan lintas disiplin yang mengaitkan isu tanah dengan perubahan iklim dan pembangunan berkelanjutan terus menguat. Negara-negara seperti Belanda dan Etiopia tampil dominan dalam produksi dan kolaborasi ilmiah, mencerminkan penguatan keterlibatan Global South dalam wacana pertanahan global. Sintesis sistematis dari 17 artikel terpilih mengidentifikasi tiga agenda riset prioritas lanjutan: analisis model tata kelola polisentris yang menyinergikan berbagai sistem dan aktor, pengukuran secara kausal dampak dan trade-off antara program sertifikasi lahan, ketahanan pangan, dan integritas ekosistem, dan studi ekonomi-politik teknologi geospasial untuk mencegah jenis baru perampasan tanah secara digital. Agenda riset tersebut diharapkan dapat memfasilitasi transisi, dari hanya sekadar administrasi pertanahan, menjadi tata kelola pertanahan yang transformatif, adaptif, dan berkeadilan bagi negara berkembang.